Examining the Effects of Urbanization on Social Structures and Environmental Sustainability: Lessons from Urban Development Projects - Ridwan Sya’rani (Penelitian dan Pengembangan Ilmu, 2024)
With urbanization continuing to increase, the relationship between urbanization, social structure, and environmental sustainability becomes increasingly important to understand in the context of sustainable urban development. This research aims to investigate the complex interactions between urbanization, social structure, and environmental sustainability, with a focus on the impact of urbanization on social and environmental structures in urban communities. Through a systematic literature review approach, researchers collected and analyzed a number of related studies from reputable international databases. The results of the analysis show that urbanization has a significant impact on the social and environmental structure in urban communities, with changes in patterns of social interaction, land use, air and water quality, and waste management. The implication of these findings is the need for an integrated approach in urban development that pays attention to social and environmental aspects simultaneously, and encourages community participation in decision-making processes related to urban development. These findings provide an important contribution to the development of policies and strategies aimed at achieving sustainable and inclusive urban development.